Replacing Needle Injection by a Novel Waterjet Technology Grants Improved Muscle Cell Delivery in Target Tissues. (April 2022) - Geng, Ruizhi; Knoll, Jasmin; Harland, Niklas; Amend, Bastian; Enderle, Markus D.; Linzenbold, Walter; Abruzzese, Tanja; Kalbe, Claudia; Kemter, Elisabeth; Wolf, Eckhard; Schenk, Martin; Stenzl, Arnulf; et al.
Current regimen to treat patients suffering from stress urinary incontinence often seems not to yield satisfactory improvement or may come with severe side effects. To overcome these hurdles, preclinical studies and clinical feasibility studies explored the potential of cell therapies successfully and raised high hopes for better outcome. However, other studies were rather disappointing. We therefore developed a novel cell injection technology to deliver viable cells in the urethral sphincter complex by waterjet instead of using injection needles. We hypothesized that the risk of tissue injury and loss of cells could be reduced by a needle-free injection technology. Muscle-derived cells were obtained from young male piglets and characterized. Upon expansion and fluorescent labeling, cells were injected into cadaveric tissue samples by either waterjet or injection needle. In other experiments, labeled cells were injected by waterjet in the urethra of living pigs and incubated for up to 7 days of follow-up. The analyses documented that the cells injected by waterjet in vitro were viable and proliferated well. Upon injection in live animals, cells appeared undamaged, showed defined cellular somata with distinct nuclei, and contained intact chromosomal DNA. Most importantly, by in vivo waterjet injections, a significantly wider cell distribution was observed when compared with needle injections ( P < .05, n ≥ 12 samples). The success rates of waterjet cell application in living animals were significantly higher (≥95%, n = 24) when compared with needle injections, and the injection depth of cells in the urethra could be adapted to the need by adjusting waterjet pressures. We conclude that the novel waterjet technology injects viable muscle cells in tissues at distinct and predetermined depth depending on the injection pressure employed. After waterjet injection, loss of cells by full penetration or injury of the tissue targeted was reduced significantly in comparison with our previous studies employing needle injections.